Analysis of co-assembly and co-localization of ameloblastin and amelogenin - Mazumder, Parichita; Prajapati, Saumya; Lokappa, Sowmya Bekshe; Gallon, Victoria; Moradian-Oldak, Janet (Frontiers in Physiology, 2014)
Epithelially-derived ameloblasts secrete extracellular matrix proteins including amelogenin, enamelin and ameloblastin. Complex intermolecular interactions among these proteins are believed to be important in controlling enamel formation. Here we provide in vitro and in vivo evidence of co-assembly and co-localization of ameloblastin with amelogenin using both biophysical and immunohistochemical methods. We performed co-localization studies using immunofluorescence confocal microscopy with paraffin-embedded tissue sections from mandibular molars of mice at 1, 5 and 8 days of age. Commercially-available ameloblastin antibody (M300) against mouse ameloblastin residues 107-407 and an antibody against full-length recombinant mouse (rM179) amelogenin were used. Ameloblastin-M300 clearly reacted along the secretory face of ameloblasts from days 1-8. Quantitative co-localization was analyzed (QCA) in several configurations by choosing appropriate regions of interest (ROIs). Analysis of ROIs along the secretory face of ameloblasts revealed that at day 1, very high percentages of both the ameloblastin and amelogenin co-localized. At day 8 along the ameloblast cells the percentage of co-localization remained high for the ameloblastin whereas co-localization percentage was reduced for amelogenin. Analysis of the entire thickness on day 8 revealed no significant co-localization of amelogenin and ameloblastin. With the progress of amelogenesis and ameloblastin degradation, there was a segregation of ameloblastin and co-localization with the C-terminal region decreased. CD spectra indicated that structural changes in ameloblastin occurred upon addition of amelogenin. Our data suggest that amelogenin-ameloblastin complexes may be the functional entities at the early stage of enamel mineralization.